Contribution of PAI Teacher Personality Competence to Student Motivation in School Exams - M. Ali Sibram Malisi; Sardimi Sardimi; Surawan Surawan; Ahmad Aldianoor (Ta'dib, 2023)
The role of a teacher in the learning process is very important, because the teacher is expected to be able to guide and direct students according to the abilities of their respective students. This research started with curiosity to find out how much and how the personality competence of PAI teachers contributes to students' learning motivation in facing school exams at SMP NU Palangka Raya. This study aims to find out how the personality competence of PAI teachers contributes to students' learning motivation in facing school exams at SMP NU Palangka Raya. This study uses a quantitative analysis approach. The sample in this study were 9th grade students of SMP NU Palangka Raya, totaling 79 students. Collecting data using a questionnaire and then analyzed using regression analysis. The results of the study show that there is a significant contribution from the personality competence of Islamic religious education teachers to students' learning motivation in facing school examinations at SMP NU Palangka Raya. The contribution or influence given was 33.9%. This shows that the teacher's personality is very important in carrying out the learning process in the classroom. Because motivation is very important in improving student achievement. For this reason, teachers are expected to foster motivation to learn in students in various ways according to the ability of the teacher and attractive to students